Analisis Kesulitan Belajar Siswa Pada Mata Pelajaran IPA di Kelas III SD Negeri 0118 Sibuhuan Julu - Nurhayati Siregar; Rizki Hamdan Saputra; Resky Fadila (Student Research Journal, 2023)
This research aims to: (1) Find out the factors of learning difficulties experienced by students. (2) the teacher's efforts to overcome students' learning difficulties. This research is field research using a qualitative approach, namely research that produces data in the form of written or spoken words from the people studied. The subjects in this research were class III students at SD Negeri 0118 Sibuhuan Julu, totaling 27 students of whom 15 men and 12 women. Data collection techniques in this research used interview, observation and documentation techniques. The data analysis technique in this research does not use numbers but instead uses descriptions in the final results. The results of this research are an analysis of (1) Factors of learning difficulties, namely, internal factors and external factors, internal factors originating from the students themselves including: intelligence, motivation, talents and student interests. Meanwhile, students' external factors include: family factors, school environment and social environment. (2) The efforts made by the teacher are that the teacher must involve students in learning activities, get students used to taking notes, establish good communication between teachers and students, conduct group learning to be more enthusiastic in the learning process, direct students so they are not stressed and provide pleasant learning atmosphere. That way students will be active in the learning process.